The Role of C Reactive Protein in Fever without Focus among Children Aged Between 1 – 3 Years (Academia Journal of Medicine, 2019)
Background: The incidence of invasive pneumococcal disease in children has come down because of polysaccharide vaccine. The increased  incidence of bacteremia among young children may be due to part of maturational immune deficiency in the production of opsonic Ig Ganti  bodies to the polysaccharide antigens present on en capsulated bacteria. Fever is a common present in gsymp to min paediatric out patient  practice and in children less 3 years of age. Approximately 20%to30% of the children may have no identifiable cause off ever after history and  physical examination. Subjects and Methods: Children in the age group of 1-3 years presenting to the outpatient department were screened  for temperature >39°C and who satisfied inclusion criteria were included in the study. Temperatures were recorded either in the axillary or  rectal areas. Informed consent was obtained from parents or guardian & clearance of Institutional Ethical Committee Review Board. Blood  samples were taken for total WBC count, ANC, ESR and CRP and at the same time samples for blood culture. Blood cultured in various media  incubated overnight and colony morphology was read. Results: CRP >6mg/d1 was observed in 25 cases of children who had SBI giving rise to  sensitivity of 75.8%, 46 children who did not have SBI have CRP
Keywords: C reactive Protein; Fever; Children